Diosgenin regulates adipokine expression in perivascular adipose tissue and ameliorates endothelial dysfunction via regulation of AMPK. Issue 155 (January 2016) - Chen, Yan; Xu, Xiaoshan; Zhang, Yuanyuan; Liu, Kang; Huang, Fang; Liu, Baolin; Kou, Junping
Graphical abstract: Highlights: Diosgenin modulates adipokine expression in PVAT against inflammation. The anti-inflammatory activity of diosgenin in PVAT depends on AMPK. Protecting PVAT function by diosgenin prevents endothelial dysfunction. Abstract: Perivascular adipose tissue (PVAT) has been recognized as an active contributor to vascular function due to its paracrine effects on cells contained within vascular wall. The present study was designed to investigate the effect of diosgenin on adipokine expression in PVAT with emphasis on the regulation of endothelial function. Palmitic acid (PA) stimulation induced inflammation and dysregulation of adipokine expression in PVAT. Diosgenin treatment inhibited IKKβ phosphorylation and downregulated mRNA expressions of proinflammatory cytokines/proteins including tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), monocyte chemoattractant protein (MCP-1), and inducible nitric oxide synthase (iNOS), while reduced gene expressions for adiponectin, PPARγ, and arginase 1 (Arg-1) were reversed by diosgenin treatment. Diosgenin enhanced AMPK phosphorylation under basal and inflammatory conditions in PVAT, whereas knockdown of AMPK by SiRNA diminished its modulatory effect, indicating that diosgenin inhibited inflammation in an AMPK-dependent manner. We prepared conditioned medium from PA-stimulated PVAT to induce endothelial dysfunction and found that pre-treatment of PVAT with diosgenin effectively restored the loss of ACh-induced vasodilation and increased eNOS phosphorylation in rat aorta. High-fat diet feeding in rats induced inflammation in PVAT and the impairment of endothelium-dependent vasodilation, whereas these alterations were prevented by oral administration of diosgenin at doses of 20 and 40 mg/kg. In conclusion, the obtained data showed that diosgenin ameliorated inflammation-associated adipokine dysregulation, and thereby prevented endothelial dysfunction. Our findings would shed a novel insight into the potential mechanism by which diosgenin protected endothelial function against inflammatory insult.